2021
DOI: 10.1007/s11604-021-01094-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery trunk enlargement on admission as a predictor of mortality in in-hospital patients with COVID-19

Abstract: Purpose To describe the prognostic value of pulmonary artery (PA) trunk enlargement on the admission of in-hospital patients with severe COVID-19 infection by unenhanced CT image. Materials and methods In-hospital patients confirmed COVID-19 from January 18, 2020, to March 7, 2020, were retrospectively enrolled. PA trunk diameters on admission and death events were collected to calculate the optimum cutoff using a receiver operating characteristic curve. According to the cutoff, the subjects on admission were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…However, in the present study, the effect of MPAD increase on mortality was examined without using a cut-off value. In addition, the mortality rates in the present study were quite high compared to those in the study by QQ Zhu et al (16) (64.1% vs. 7.8%) due to the high mean age of the patients included in the present study (69.82 years vs. 46.99 years) and the patients requiring intensive care treatment.…”
Section: Discussioncontrasting
confidence: 66%
“…However, in the present study, the effect of MPAD increase on mortality was examined without using a cut-off value. In addition, the mortality rates in the present study were quite high compared to those in the study by QQ Zhu et al (16) (64.1% vs. 7.8%) due to the high mean age of the patients included in the present study (69.82 years vs. 46.99 years) and the patients requiring intensive care treatment.…”
Section: Discussioncontrasting
confidence: 66%
“…On the other hand, TIB was associated with a significantly increased prevalence of pulmonary artery dilatation, a radiologic sign recently recognized as a predictor of clinical severity and mortality in COVID-19 patients [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Esposito et al, which included 1461 patients, determined that an MPAD ≥ 31 mm in COVID-19 patients was an independent predictor of mortality (15). The study by Zhu et al demonstrated that MPAD ≥ 29 mm is a significant predictor of mortality (10). Truong et al demonstrated that the predictive value of MPAD of 31 mm or greater in diagnosis PH and associated with 2-3 fold increased mortality risk compared to normal (11).…”
Section: Discussionmentioning
confidence: 99%
“…CT is widely used, especially in the emergency department, to make a risk assessment, and evaluate lung involvement and differential diagnosis. PA enlargement is a predictor of hemodynamic instability such as; right ventricular failure, pulmonary hypertension (PH), and embolism (9,10,11). Although PA dilatation reflects vascular injury, abnormal coagulation, hypoxia, and inflammation, the optimal cut-off value of PA diameter in COVID-19 patients is unknown.…”
Section: Introductionmentioning
confidence: 99%